THE INFLUENCE OF VALUE FOR MONEY MODERATE PURCHASE DECISION ON XIAOMI PRODUCTS - Jokhu, Jean Richard; Agung, Geraldi (Lentera Jurnal Manajemen, 2025)
The proliferation of local skincare products has reach nationwide awareness. Practitioners have find an increasing attention to facilitating skincare consumer purchase decision exposures with influencer and word of mouth strategies. However, previous research on the impact of influencers on consumers' word of mouth is limited. This study aims to provide new insights into the drivers of customer purchase decisions on local skincare products. influencers and electronic word of mouth. The questionnaire spread to determine the appropriate influencers' effect. An online survey was held on to test the proposed model. Results indicate that influencers and word of mouth predict consumer purchase decisions. Word of mouth mediated the effect of influencers and consumer purchase decisions. This study sheds on a new path to the understanding of social media influencers through the lens of digital channels. Word of mouth is able to boost the effect of influencers on all social media channels.